Effect Of Airport Signage Quality on Passenger Satisfaction at Juanda International Airport - Luthfikar Abdul Lathief; Maulana Anifa Silvia; Agus Triyono; Lady Silk Moonlight; Yuyun Suprapto; Petek Tezcan (Jurnal Penelitian, 2026)
Airport signage is a core wayfinding facility that can reduce uncertainty and support passenger movement in complex terminal environments. This study examined the effect of signage quality—operationalized through clarity, placement, and lighting—on passenger satisfaction in the departure area of Terminal 1, Juanda International Airport. A quantitative cross-sectional design was applied to 100 passengers using a 24-item, five-point Likert questionnaire. Twelve items measured signage quality and twelve measured passenger satisfaction. Instrument quality was assessed through item-total validity and Cronbach’s alpha, followed by normality testing, Pearson correlation, and simple linear regression. All items were valid; reliability was high for signage (α = 0.957) and passenger satisfaction (α = 0.936). Signage quality was strongly associated with passenger satisfaction (r = 0.959, 95% CI [0.940, 0.972], p < 0.001), and explained 92.0% of the observed variance (R² = 0.920). Lower-scoring items concerned ease of locating signs, orientation, reduction of confusion, and overall satisfaction with directional clarity. The novelty of the study lies in isolating the physical characteristics of airport signage as a specific service-quality determinant in an Indonesian terminal context rather than treating signage as a minor part of a broad facility index. The findings extend airport service-quality research by linking tangible information infrastructure with passenger satisfaction and provide a practical basis for signage audits, decision-point placement, lighting improvement, and passenger-centered terminal planning. Because both variables were measured through the same cross-sectional questionnaire, the unusually high R² should be interpreted cautiously and verified through multi-airport and multi-method studies.